Experimental Investigation of Dry and Cryogenic Friction Stir Welding of AA7075 Aluminium Alloy - A. Praveen Raj Navukkarasan; K. Shanmuga Sundaram; C. Chandrasekhara Sastry; M. A. Muthu Manickam (Advances in Materials Science and Engineering)
An attempt has been made to investigate dry and cryogenic friction stir welding of AA 7075 aluminium alloy, which is predominantly availed in aerospace and defence component industries. These industries avail friction stir welding for joining two nonferrous materials, and minimal deviations and maximum strength are the preliminary and long time goal. A cryogenic friction stir welding setup was developed to conduct the joining of two aluminium alloy pipes. An increase of 0.76–42.93% and 3.79–31.24% in microhardness and tensile strength, respectively, is ascertained in cryogenic friction stir welding in correlation to dry friction stir welding of aluminium alloys. TOPSIS evaluation for the experimental run indicated tool profile stepped type, pipe rotation speed of 1000 rpm, welding speed of 50 mm/min, and axial force of 8 kN as close to unity ideal solution for dry and cryogenic friction stir welding of AA 7075 aluminium alloys. The friction stir-welded component under the cryogenic environment showcased drop in temperature, curtailed surface roughness, and fine grain structure owing to reduction in temperature differential occurring at the weld zone. A curtailment of 50.84% is ascertained in the roughness value for cryogenic friction stir welding in correlation to dry friction stir welding of AA 7075 alloy. A decrement of 21.68% is observed in the grain size in the cryogenic condition with correlation to the dry FSW process, indicating a drop in the coarse structure. With the curtailment of grain size and drop in temperature differential, compressive residual factor and corrosion resistance attenuated by 40.14% and 67.17% in the cryogenic FSW process in correlation to the dry FSW process, respectively.